2016
DOI: 10.1126/science.aaf4384
|View full text |Cite
|
Sign up to set email alerts
|

A large fraction of HLA class I ligands are proteasome-generated spliced peptides

Abstract: catalyzed peptide splicing.Abbreviations: electron-transfer higher-energy collision dissociation (EThcD); higher-energy collision dissociation (HCD); false discovery rate (FDR); HLA class I (HLA-I); lymphoblastoid cell line (LCL); mass spectrometry (MS); molecular weight (MW); proteasome-catalyzed peptide splicing (PCPS). 2The proteasome generates the epitopes presented on HLA class I molecules that elicit CD8 + T cell responses. While reports of proteasome-generated spliced epitopes exist, they have been rega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
400
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 306 publications
(417 citation statements)
references
References 41 publications
14
400
3
Order By: Relevance
“…This makes it very difficult to compare the splicing of peptides with one or two amino acid substitutions, as these may target the peptide to another catalytic subunit, and the C-terminal reactant itself might not access as efficiently to the primed binding site of each catalytic subunit. Moreover, when Liepe et al (37) compared spliced peptides eluted from distinct cell lines, they observed significant differences in the nature of the amino acids found at key positions (P 1 , P 1 Ј (Fig. 5), N terminus, and C terminus).…”
Section: Deciphering the Rules Of Peptide Splicing By The Proteasomementioning
confidence: 99%
See 2 more Smart Citations
“…This makes it very difficult to compare the splicing of peptides with one or two amino acid substitutions, as these may target the peptide to another catalytic subunit, and the C-terminal reactant itself might not access as efficiently to the primed binding site of each catalytic subunit. Moreover, when Liepe et al (37) compared spliced peptides eluted from distinct cell lines, they observed significant differences in the nature of the amino acids found at key positions (P 1 , P 1 Ј (Fig. 5), N terminus, and C terminus).…”
Section: Deciphering the Rules Of Peptide Splicing By The Proteasomementioning
confidence: 99%
“…Again, a major limitation in the identification of spliced peptides by peptidomics is the fact that databases used for matching only contain linear protein fragments. Recently, Liepe et al (37) addressed this issue by creating a custom peptide database, which includes any possible short peptides created by the splicing of non-contiguous peptide fragments from the proteins expressed in the cell lines studied. To restrict the size of the database, only peptides produced by the cis-splicing of fragments separated by 25 amino acids or less were taken into account.…”
Section: Minireview: Peptide Splicing By the Proteasomementioning
confidence: 99%
See 1 more Smart Citation
“…Even though proteasome-generated spliced epitopes have been reported, such protein-splicing derived epitopes are generally rare events. Interestingly, a recent study shows that the proteasome-generated spliced peptide pool could account for one-third of the entire HLA class I immunopeptidome in terms of diversity and one-fourth in terms of abundance [151]. However, it is not clear how many or what percentages of tumor antigens are generated through this mechanism.…”
Section: Antigenic Peptides Derived From Protein Splicingmentioning
confidence: 99%
“…However, it is not clear how many or what percentages of tumor antigens are generated through this mechanism. Nonetheless, proteasome-generated MHC class I-restricted spliced cancer peptides may represent a previously untapped source of epitopes for use in vaccines and cancer immunotherapy [151]. MHC class II-restricted spliced T cell epitopes from cancer cells have not been reported so far.…”
Section: Antigenic Peptides Derived From Protein Splicingmentioning
confidence: 99%